THE USE OF SEMANTIC MAPPING TO IMPROVE STUDENTS’ VOCABULARY MASTERY IN SENIOR HIGH SCHOOL - Sisi Yusra, Irwandi, Eliza, Absharini Kardena (LP3M STKIP Muhammadiyah Muara Bungo, 2023)
This research was based on facts that the students’ vocabulary mastery in low level.. This was due to the fact that teaching vocabulary is not only about having a lot of vocabulary but students must also understand the form and meaning of the word. In addition, semantic mapping is not applied in English textbook to teaching vocabulary at Senior high school. The goal of this research was to improve students’ vocabulary mastery. To achieve this goal, this research offered the use of semantic mapping in understanding word forms and word meanings so that students can improve their vocabulary mastery. Through analysis of the data, the researcher found that vocabulary can be taught using word formation and meaning of the word. There are several ways to explain word formation namely etymology, coinage, borrowing, compounding, blending, clipping, backformation, conversion, acronym, and derivation. In addition, semantic mapping used in understanding meaning of the word through antonym, synonym, meronym, taxonomy,monosemy, homonym, and polysemy. It is concluded that semantic mapping can be used in explain the word and its meaning. In addition, Semantic mapping is not only uses tree diagrams in explaining words but can also use various forms such as star diagram, spider diagram, fishbone diagram, cycle diagram and vocabulary graphic organizer.